PENGARUH CURRENT RATIO, DEBT EQUITY RATIO, DAN GROSS PROFIT MARGIN TERHADAP HARGA SAHAM PADA SEKTOR INDUSTRI DASAR DAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2012-2021 - Yayuk Febriani; Suwanto Sirait; Frangky Yosua Sitorus; Melinda Malau (Fundamental Management Journal, 2023)
Purpose of these studies was to analyse effects of currents ratio, debts equity ratio and gross profit margins on stocks price in manufacturing companies in basic and chemical industries in 2012-2021 (case studies on companies that apply the concept of good corporate governance). In these studies, using quantitative methods with data collections technique using purposive sampling, namely collection by having sample criteria: 1). Companies in basics and chemicals industries sector list on Indonesia Stock Exchanges (IDX) in 2012-2021. 2). Companies in basic and chemical industries sector that have implemented the concept of good corporate governance. 3). Have complete financial statements ending December 31 and published consecutively during the 2012-2021 research period. 4). Have complete financials data to calculates variable in these studies, namely 2012-2021. The test results in these studies concluded that currents ratio has a significances positive effect on stocks price, debts equity ratio has no significances effects on stocks price, gross profitable margins have a significances effect on stocks price. Simultaneously all independent variables, namely Currents Ratio (X1), Debts Equity Ratio (X2), and Gross Profit Margins (X3), d simultaneously have a positive effect on stocks price (Y). Based on result of these studies indicate that currents ratio, debts equity ratio, and gross profit margins have an influence on stocks price. This implies that this variable can be used by investors to carry out analysis before purchasing a company's stock price, in order to benefit from the invested capital. Keywords: Current Ratio, Debt